Aplicación de un sistema de costos por procesos en la hacienda Agricola Tilipulo, ubicada en el cantón Latacunga, provincia de Cotopaxi, para el periodo julio-diciembre del 2012. - Taipe Coyachamin, Jessi Karina (2013)
The present research consists in the application of costing methodology in the farm Tilipulo. It is currently very important to have a cost system that provides real, reliable and timely information as to the cost involved in producing a particular product since this provides a basis for the improvement of processes, optimization of resources and take appropriate decisions. Carrying out investigative process was determined, the state which ignore the cost of production for each cultivated section. It was a serious problem that affect the economic situation of the same, since not having records and parameters on the use of materials prevented to identify real cost and the degree in which it wasted resources in the different stages of production, is for this reason that has been considered essential to implement a system of costing to determine the cost of production, cost of sales and the utility or loss generated by this activity, so they have a source of information for decision making and serve as a basis for cost control. The application of the process cost system in the estate Tilipulo will allow the manager take decisions regarding prices and utility margins, the continuous improvement of the production process that has been established three clearly defined stages as well as to facilitate the control and optimization of materials at each stage of production, thus achieving economic and financial stability.